2020
DOI: 10.1002/bmc.4916
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of gallic acid, methyl gallate, and 1,3,6‐tri‐O‐galloyl‐βd‐glucose from Turkish galls in rat plasma using liquid chromatography‐tandem mass spectrometry and its application to pharmacokinetics study

Abstract: Turkish galls (TG) is a traditional Uygur medicine typically used in clinics for dental disease and chronic ulcerative colitis. In this study, a novel liquid chromatography‐tandem mass spectrometry method was developed and validated for the simultaneous quantification of gallic acid, methyl gallate, and 1,3,6‐tri‐O‐galloyl‐β‐d‐glucose in rat plasma, which are the major bioactive compounds of TG. After a feasible protein precipitation using acetonitrile for sample preparation, chromatographic separation was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Gallo-tannins are mixtures of polygallic acyl groups, with two main types: one with TEGG as the core and the other with PEGG as the core [ 6 , 7 ]. Pharmacological studies have demonstrated that TG exhibits a range of pharmacological activities, including antioxidant, anti-inflammatory, antitumor, antibacterial, antiviral, local anesthetic, insecticidal, hypoglycaemic, and wound healing properties [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gallo-tannins are mixtures of polygallic acyl groups, with two main types: one with TEGG as the core and the other with PEGG as the core [ 6 , 7 ]. Pharmacological studies have demonstrated that TG exhibits a range of pharmacological activities, including antioxidant, anti-inflammatory, antitumor, antibacterial, antiviral, local anesthetic, insecticidal, hypoglycaemic, and wound healing properties [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%